FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PROYEK PEMBANGUNAN BOX CULVERT JEMBATAN JALAN SUDIRMAN DAN JALAN AGUSSALIM KECAMATAN BANGKINANG KOTA - Febryanto, Febryanto; Azriadi, Emon; Adrian, Nurul; Yusnita, Amelia; Alenya, Nia; Fadri, Roy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Bridges are structures built to connect transportation activities due to obstacles such as rivers, lakes, swamps and other obstacles. As part of drainage systems and bridge infrastructure, box culverts help transport and control water flow. In implementing bridge construction projects there are several tendencies that influence performance, one of which is time management. The aim of this research is to identify the components that influence the length of time the box culvert bridge construction project on Jalan Sudirman and Jalan Agussalim, Bangkinang City subdistrict lasts. This research adopts a descriptive quantitative approach, a quantitative method rooted in the philosophy of positivism was chosen because it allows the collection of numerical data in a systematic and structured manner. Data collection was carried out through questionnaire data. The results of the research show that the main components causing the box culvert bridge construction project on Jalan Sudirman and Jalan Agussalim, Bangkinang Kota subdistrict to be delayed are the lack of expertise and skills as well as work motivation for workers in the field with a respondent result of 54% lack of expertise and skills and desire to work among workers in the field, according to 54% of respondents, the owner's work plan statement often changes based on the results of 51% of respondents and material accuracy with a respondent result of 51%.Keywords: Time Management, Box Culvert, Construction Project Delays